SOME POST-LARVAL AND JUVENILE STAGES OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER), WITH NOTES ON THE CHANGES IN BODY FORM - Balakrishnan, V; Rao, K V Narayana (Indian Journal of Fisheries, 2011)
The Indian mackerel, Rastrelliger kanagurta (Cuvier), belonging to the family Scombridae, is one of the commercially important food fishes of India and a few other countries bordering the Indo-Pacific. The life history of this species has not been fully investigated so far. The earliest description of a Rastrelliger egg is by Delsman(1926) from the Java Sea. Subsequently, Delsman (1931) expressed doubts about the .correctness of his earlier identification. Manacop (1956) has described, from the Philippine waters, two specimens of R. chrysozonus measuring 26 mm and 48 mm in length. Devanesen and John (1940), Balakrishnan (1957) and Kuthalingam (1956) have recorded the occurrence of eggs and larvae of R. kanagurta from the Indian waters. Jones and Kumaran (1964) have given figures of two juveniles measuring 34 mm and 65 mm in length. A single larva measuring 9.3 mm collected from the Andaman Sea during Vityaz Expedition has been described by Gorbunova (1963). The eggs and larvae of Rastrelliger, collected from the Gulf of Thailand, have been described by Boonprakob (1962, 1965) and the Rastrelliger larvae collected from the same area during the Naga Expedition have been described by Matsui(1963). In this paper a series of early stages of the Indian mackerel is presented. However, this does not include the pro-larvae reported earlier vide Balakrishnan, 1957) as the material is not available now.